Efficiency in the use of phosphorus in native maize cultivated in Andosols of Central Mexico (Agroindustrial Science, 2025)
Phosphorus use efficiency is controlled by the manner in which the plant acquires and utilizes the nutrient under limiting conditions. This study evaluated biomass and P accumulation, partitioning, and remobilization processes, and their relationship with P utilization efficiency (PUTE) in maize. Three early and three late maturing maize genotypes were grown on a P-deficient soil, with limited (25 kg P2O5 ha-1) and optimal (50 kg kg P2O5 ha-1) P fertilization. The study identified genotypic variation among the tested maize genotypes for PUTE. Under P deficiency environments, late maturing genotypes showed the greatest amount of dry matter and P in vegetative organs and a less remobilization of biomass to grain. In contrast, early maturing genotypes maintained unchanged proportion of biomass and P partitioning into various organs and a higher P remobilization to grain, at both P levels. Regardless of P application rate, biomass and P remobilization to the grain was higher in early maturing genotypes (22 y 21 %) than in late ones (18 y 15 %). Greater variation on PUTE was linked to an enhanced dry matter partitioning in the plants and a higher proportion of P allocated into young and active tissue, under P-limited acid soils.
Keywords: Zea mays; phosphorus; accumulation pattern; partitioning; remobilization